Opportunities and Limitations for Achieving Land Degradation-Neutrality through the Current Land-Use Policy Framework in Kenya - Gichenje, Helene (2019)
The United Nations Convention to Combat Desertification (UNCCD) land degradation neutrality (LDN) scientific conceptual framework underscores that LDN planning and implementation should be integrated into existing planning processes and supported by an enabling policy environment. Land-use planning, which requires the integration of different policy goals across various sectors concerned with land-use, can be an effective mechanism through which decisions with respect to LDN can be coordinated. Using Kenya as a case study, we examined current policy instruments that directly or indirectly impact on the use of land in a rural context, to assess their potential to implement LDN objectives. The qualitative content analysis of these instruments indicated that they are rich with specific legal provisions and measures to address LDN, and that there are a number of relevant institutions and structures across governance levels. However, the main shortcoming is the disjointed approach that is scattered across policy areas. Key policy improvements needed to support effective implementation of LDN include: a national soil policy on the management and protection of soil and land; a systematic and coordinated data collection strategy on soils; mobilisation of adequate and sustained financial resources; streamlined responsibilities, and governance structures across national, regional and county levels.